Gabay sa tagapagsanay ng mga legal advocates sa komunidad - Ealdama, Yolanda G.; Rago , Lucia Cynita C.; Pecimo, Shella O. (Quezon City Women's Legal Bureau, 1998)
Guidebook for trainer of legal advocates in Philippines community.
Includes bibliographical references (p. 206-208).
In Filipino.
Keywords: Legal aid -- Philippines -- Handbooks, manuals, etc; Legal assistance to women -- Philippines -- Handbooks, manuals, etc